Bilateral Dome-Shaped Macula with Serous Macular Detachment in a Child - Zafer Cebeci; Nur Kir (Case Reports in Ophthalmological Medicine)
Dome-shaped macula is a structural disorder and optical coherence tomography (OCT) helps us to confirm macular convexity. We describe the first case of bilateral dome-shaped macula in an 8-year-old boy with subretinal fluid. The patient was diagnosed using spectral-domain OCT and received indocyanine green angiography-guided half-fluence photodynamic therapy as treatment.